Analysis of the content of the Arabic textbook for the third intermediate grade in the light of national values (Journal of the College of Basic Education, 2024)
The study aimed to analyze the content of the Arabic language textbook for the middle third grade in the light of national values, in order to find out the national values and their availability in this book, The researcher followed the descriptive curriculum, and the researcher developed an open questionnaire that included a number of values that must be available in the Arabic language textbook for the third grade and presented it to a number of experts in the Arabic language and teaching methods, and after the approval of the experts, he calculated the national values, emptied them into a table, calculated their repetitions, extracted the percentages of each value and classified them by priority for each value, and the researcher reached several results, and the researcher recommended a number of recommendations and proposals